Mechanisms of MicroRNA Biogenesis and Stability Control in Plants - Zhang, Lu; Xiang, Yu; Chen, Shengbo; Shi, Min; Jiang, Xianda; He, Zhuoli; Gao, Shuai (Frontiers in Plant Science, 2022)
MicroRNAs (miRNAs), a class of endogenous, non-coding RNAs, which is 20 to 24 nucleotide long, regulate the expression of its target genes post-transcriptionally and play critical roles in plant normal growth, development, and biotic and abiotic stresses. In cells, miRNA biogenesis and stability control are important in regulating intracellular miRNA abundance. In addition, research on these two aspects has achieved useful results. In this review, we focus on the recent research progress in our understanding of miRNA biogenesis and their stability control in plants.